The Implementation of Curriculum Merdeka in English Subject; A Case Study of The Elementary English Teacher in Batam - Purba, Hilarius Raditya Priambada; The, Desmond; Tansri, Frandy; Siska, Kharisma Anjar; Zaki, Leil Badrah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
As times change, the education curriculum in Indonesia has undergone many modifications, with the latest being the Kurikulum Merdeka. This curriculum is a government response aimed at addressing the decline in meaningful learning during the pre-pandemic, pandemic, and post-pandemic phases. This study aims to examine the implementation of the Kurikulum Merdeka in the English language subject at a private elementary school in Batam City. The research method used is descriptive qualitative with a case study approach. Data collection was conducted through classroom observations and interviews with teachers. The results indicate that the implementation of the Kurikulum Merdeka at the school is not yet fully realized, particularly in terms of applying student-centered learning. On the first day, teaching methods were still predominantly teacher-centered, although there was an increase in interaction between students and teachers on the second day. Additionally, this study found that teachers hold a positive view of the curriculum but face several challenges, such as inadequate facilities and resources, as well as difficulties in student adaptation. This study suggests the need for adequate teacher training and the provision of supportive facilities to enhance the implementation of the Kurikulum Merdeka. Furthermore, further research is needed to explore specific strategies to address these challenges and improve student learning outcomes. By gaining a deeper understanding of the challenges and factors affecting the implementation of this curriculum, it is hoped that targeted intervention strategies can be developed to improve the quality of education in Indonesia.